Prevention of Catheter-Associated Urinary Tract Infection - suwannakeeree, wongduan -; Jullmusi, Orapin (NU Journal of Nursing and Health Sciences, 2023)
Patients with indwelling urinary catheters are susceptible to urinary tract infection. It is an important indicator of the quality of patient care in a hospital. Prevention of catheter-associated urinary tract infection (CAUTI) that covers all factors related to the infection is important. Healthcare personnel, especially nurses, must have knowledge and understanding about caring for patients with indwelling urinary catheters including the mechanism of CAUTI, diagnosis criteria, and factors related to CAUTI. Additionally, the CAUTI prevention guideline should be developed and practice following the guideline should be monitored for increasing patients’ safety and reducing risk of CAUTI